Neo-liberal Governance and James Bay Cree Governance: Negotiated Agreements, Oppositional Struggles, and Co-Governance. - Feit, Harvey A. (University of British Columbia Press, 2010)
Diverse relations have developed between Indigenous peoples and the institutions of nation-states and markets shaped by the globalization of neoliberal visions and practices. In this chapter I analyze James Bay Cree governance in relation to state and neoliberal forms of governance in Québec and Canada. In the early 1970s Crees fought their exclusion from regional governance and a say in a hydro-electric project. They created dialogues and negotiations with governments that led to a 1975 agreement that very imperfectly acknowledged fragments of Cree governance as well as established practices of messy co-governance that went back decades. When the 1975 co-governance agreement provisions were ignored, the Crees opposed major government and corporate projects from the mid-1980s to 2000 and they stopped a new hydro-electric project. Their continuing opposition was also intended to, and did, create renewed dialogues and in 2001-02 negotiations addressing Cree agendas. These negotiations were entered into by the governments and developers partly because Cree posed a significant risk to new large-scale natural resource developments and partly because the growing dominance of neoliberal discourses and practices made new state arrangements with non-state entities possible and desirable. The Crees are now trying to implement another imperfect co-governance and co-development funding agreement. When Crees signed the 1975 agreement, they were not denying themselves other options for action if they later decided they needed them. Governments, corporations, and numerous social analysts and Indigenous rights critics thought that Crees had compromised themselves irrevocably and had weakened their capacity for the kind of autonomy and political campaigns that Crees did later develop effectively. For many Crees, the agreements express: their lived self-governance even in the midst of fragmented recognition; their relational cosmology of acknowledging coexistence; their historical experience with co-governance and its messy possibilities; and the need to develop new economic opportunities in co-governance with non-Crees. Giving up on agreements to adopt the positions urged by critiques who emphasize cosmopolitan or more totally oppositional strategies would diminish Crees, for it would devalue their visions, historical experiences, and their achievements. It would shift their struggle for collective survival more to the terrain of neoliberal governmentalities and the equally modernist critical theories of neoliberalism embedded in universalist visions. Cree engagements embody decades of lived experiences of Cree governance and co-governance as well as visions for the future.
This chapter is included in the MacSphere Repository with the permission of UBC Press, March 6, 2019. In this chapter I draw on the insights and work of many Cree people and other colleagues. I want to acknowledge my special debt for comments on this chapter by Philip Awashish, Mario Blaser, Brian Craik, Jasmin Habib, and Colin Scott.
Keywords: Neoliberalism; Globalization; Indigenous Governance; Messy Co-Governance; Opposing Developments; Negotiating Indigenous Agreements; Modernist Political Critique; Self-governance Histories; James Bay Cree; Québec